التحول الرقمي في ظل جائحة كورونا - جبير، علي سعدي عبدالزهرة (جامعة عمار ثليجي الأغواط - كلية الحقوق والعلوم السياسية, 2021)
التحول الرقمي يعني الاستغناء عن الطرق التقليدية والتوجه نحو الطرق الحديثة الإلكترونية، الأمر الذي يوفر الوقت والتكلفة والجهد بشكل كبير وبحسن الكفاءة التشغيلية وينظمها، ويعمل على تحسين الجودة وتبسيط الإجراءات للحصول على الخدمات المقدمة، وأن التحول الرقمي حاجة ضرورية لاسيما في ظل الأزمات، وأزمة كورونا دليل على ذلك، إذ أن جائحة فيروس كورونا التي انتشرت في بقاع الأرض وبثت الرعب والخوف في النفوس البشرية وأغلقت المؤسسات والشركات بسببها، إلا أن التكنولوجيا كان لها رأي أخر، إذ اتجهت معظم دول العالم ولاسيما الدول المتقدمة إلى العمل والتعليم وتوفير الخدمات عن البعد، كما إن جائحة كورونا اختزلت عشر سنوات على الأقل في عمر التحول الرقمي إذ تسابقت الدول الزمن لوضع أسس هذا الانتقال وأرغمت الجميع على تكريسها على الأقل لتسيير بعض الأعمال والمعاملات اليومية داخل الإدارات والمؤسسات، لتلبية حاجيات الناس وفق شروط الحظر والتباعد لضمان استمرارية القطاعات الحياتية مع تواصل خطر الجائحة. Digital transformation means dispensing with traditional methods and moving towards modern electronic methods, which greatly saves time, cost and effort, improves and organizes operational efficiency, improves quality and simplifies procedures for obtaining the services provided, and that digital transformation is a necessary need, especially in light of crises, the Corona crisis is evidence Moreover, as the Coronavirus pandemic that has spread to parts of the earth, spreading terror and fear in human souls and closing institutions and companies because of it, technology had a different opinion, as most countries of the world, especially developed countries, tended to work, education and provide services from afar, as well as The Corona pandemic reduced at least ten years in the age of digital transformation, as countries scrambled to lay the foundations for this transition and forced everyone to devote at least some of the daily work and transactions within departments and institutions, to meet the needs of people in accordance with the conditions of prohibition and separation to ensure the continuity of life sectors while the threat of the pandemic continues.
Keywords: التقنيات الرقمية -- فيروس كورونا "كوفيد-19" -- الإدارة الإلكترونية -- الموارد البشرية